NURSES EXPERIENCE IN IMPLEMENTING A TRIAGE ON MASS VISITATION IN THE EMERGENCY DEPARTMENT OF NGANJUK DISTRICT HOSPITAL TYPE B - Agus Khoirul Fuadi; Retty Ratnawati; Tony Suharsono (Journal of Nursing Science Update (JNSU), 2018)
Nganjuk district hospital is the referral hospital in Nganjuk, so the consequences that must be accepted is the potential of a patient mass visitation. Mass visitation is a condition where there are lot of patients arrived at the same time, it can be caused by various causes or diseases that came from a single factor or more. These factors include the increase number of referral patientâ€™s arrival, the increase number of patient's arrival at its own initiative, some disaster/accident/plague victims, where they came to the emergency department with different criticalness. There is one question that is very important, which is how one nurse in that is placed in an emergency department of a hospital could perform a triage to handle a number of patients that are coming together. Of course, these conditions will bring an interesting experience to be explored by researchers. This study is a qualitative research that used an interpretative phenomenological approach. A deep interview was involving 4 triage nurses. The data were collected and analyzed by using a thematic analysis approach. The transcript of the interview results was analyzed by using a qualitative analysis, such initial codes were made in each participant's statement and it was interpreted in the form of a theme. The study resulted in four themes, namely Changed Triage Mechanism, Triage System Inadequate-yet, The Expectation of Emergency Room Policy Changing, KIE Advance Strategies. Where finally, these themes are narrowed down to one major theme namely The Spirit of Change in the Middle of Inadequate Triage System in Mass visitation. These description indicates the dynamics of triage nurses in the emergency department of Nganjuk district hospital in the form of a spirit of change in the middle of inadequate triage system that is used to handle a mass visitation.The researchers recommend further research that is directed to influence a triage system on a mass visitation towards the waiting time and mortality number in the emergency department of Nganjuk district hospital. The researchers also suggest that Nganjuk district hospital should create a Standard Operating Procedure (SOP) for the triage system to handle a mass visitation.Â Keyword : Triage, mass visitation